The star-crossed saints of Seville: typology of secular and sacred in early modern Catholicism. Issue 1 (2nd January 2019) - Greenwood, Jonathan E.
Abstract: A curious image appeared amid the celebrations of the beatification of Jesuit founder Ignatius Loyola ( c .1491–1556), in Seville, Spain, in February 1610. The different saintly founders of religious orders were represented as signs of the zodiac. Although no physical specimen survives, we can learn about the convergence of the secular with sacred imagery in early modern Catholicism. This representation is an example of typology, wherein varying registers, in this case, visual ones, are applied simultaneously to tie together disparate ideas and symbols. Although usually employed to contrast the Old and New Testament, typology had other uses in Catholicism as seen in Seville. This article thus helps one understand a different and more mundane imagining of early modern saints with the aid of representations of the zodiac, which has not yet been the subject of detailed study. This article attempts to rectify oversights in the scholarship with a case study involving the Society of Jesus and its founder, Ignatius, in Seville and the implementation of a typological representation produced for the beatification of Ignatius. This likeness sought to draw connections between religious and secular iconographies in order to articulate aspects of twelve founders from disparate periods in Christian history.